Designing a High-Power Sodium-Ion Battery by in Situ Metal Plating - Francesco Mazzali (ACS Applied Energy Materials, 2019)
Sodium ion batteries represent a drop-in technology and a more sustainable alternative to Li-ion, but higher energies and power levels are required to meet the demands required by a greener electrification. Here, the design of an anode-free sodium-ion battery is presented and its performances discussed in terms of reduced mass and high power capabilities. The cell consists of an Iron Hexacyanoferrate - reduced Graphene Oxide composite as cathode material whose synthesis is tailored to achieve minimal structural defects (3%) and water content. Its high-potential redox couple FeLS(C) is stabilized at high rates, granting the full cell with high discharge voltage and power. As negative substrate, a carbon coated aluminum foil was adopted for in situ plating/stripping of Na metal, showing very small voltage hysteresis up to an applied current of 2 mA/cm2. Overall, this simplified full cell architecture can deliver up to 340 Wh/kg and 500 W/kg at nominal 1C retaining 80% in 250 cycles, with the possibility of delivering 9000 W/kg at 20C. Bridging the boundaries between batteries and supercapacitors, this research aims to expand the range of possible applications for Na-ion technology.